The Influence of Technical Competence and Work Motivation on the Job Readiness of Grade XII Students (A Survey Conducted at Public and Private Vocational High Schools in the Tambora District, West Jakarta) - Muhammad Aziz Andriansyah; Hikmah Mawardah; Nani Kurniasih; Triana Damayanti; Syarifuddin Syarifuddin; Iyos Rosidah; Riska Winda Sari; Hendro Prasetyono (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
The persistently high unemployment rate among vocational high school (VHS) graduates in Indonesia, which reached 9.01% in 2024, indicates a critical disconnect between vocational education and labor market demands, highlighting an urgent need to investigate the factors influencing graduate work readiness. This research investigates the influence of vocational competence and work motivation on the work readiness of twelfth-grade students at public and private vocational high schools in Tambora District, West Jakarta. Prompted by ongoing graduate unemployment linked to a skills mismatch, the study utilized a quantitative survey design. The population consisted of all 102 twelfth-grade students in the Accounting and Financial Institutions and Office Management and Business Services programs, surveyed via a saturated sample. Data gathered from questionnaires were analyzed using multiple correlation, coefficient of determination, and multiple linear regression. Results show a strong positive relationship (r = 0.788) between the independent variables and work readiness. With an R² of 0.792, vocational competence and work motivation explain 79.2% of the variance in readiness, underscoring the critical role of competency development. The study concludes that vocational schools should prioritize industry-aligned, competency-based learning to better prepare students for the workforce.